KUALITAS PELAYANAN WISATA RELIGI PADA ADVENTURE OF LIFE TOUR & TRAVEL JAKARTA - Anugerah Dwi Ester Kemas; Rudhi Achmadi (LPPM and Travel Operation Department Universitas Asa Indonesia, 2020)
This research is a type of analytical descriptive research conducted at the Adventure of Life Tour & Travel Jakarta. This study is intended to examine consumer perceptions about service quality. Service quality has five dimensions which include direct tangibles, reliability, responsiveness, assurance, and empathy. The population of this research is consumers from Adventure of Life Tour & Travel, with a sample of 69 respondents and their sampling technique is an accidental sampling. The method of collecting data using a questionnaire that is distributed to consumers through Google form. The results of the study with a descriptive analysis of the percentage show the quality of service which includes direct tangibles, reliability, responsiveness, assurance, and empathy included in either category. Based on the researcher's test results, the average value for tangible indicators is 4.79, reliability indicators are 4.80, indicators are 4.82, indicators are assurance and 4.87, and indicators of empathy 4.75. The conclusion in this study is the quality values ​​obtained by the Adventure of Life Tour & Travel are already in the